2020
DOI: 10.3389/fonc.2020.00621
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 Is a Prognostic Biomarker Associated With Immune Infiltration in Luminal Breast Cancer

Abstract: Background: Sirtuin 7 (SIRT7), a protein-coding gene whose abnormal expression and function are associated with carcinogenesis. However, the prognosis of SIRT7 in different breast cancer subtypes and its correlation with tumor-infiltrating lymphocytes remain unclear. Methods: The expression and survival data of SIRT7 in patients with breast cancer were analyzed using Tumor Immune Estimation Resource (TIMER), Gene Expression Profiling Interaction Analysis (GEPIA), The Human Protein Atlas (HPA), UALCAN, Breast C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Since inhibition of TIE2 was found to result in inhibition of cancer cell migration and tumour invasion in our previous findings, 39 , 40 the anti-metastatic effect of MSN-siRNA/Apt was assessed in vitro. Notably, Dox was found to impact cell migration and invasion in previous studies; 41 , 42 consequently, Dox was not loaded into the siRNA formulations in our in vitro anti-metastasis study. First, the TIE2 protein expression among different treatments was investigated to determine the knockdown effect of siTIE2.…”
Section: Resultsmentioning
confidence: 76%
“…Since inhibition of TIE2 was found to result in inhibition of cancer cell migration and tumour invasion in our previous findings, 39 , 40 the anti-metastatic effect of MSN-siRNA/Apt was assessed in vitro. Notably, Dox was found to impact cell migration and invasion in previous studies; 41 , 42 consequently, Dox was not loaded into the siRNA formulations in our in vitro anti-metastasis study. First, the TIE2 protein expression among different treatments was investigated to determine the knockdown effect of siTIE2.…”
Section: Resultsmentioning
confidence: 76%
“…For the two writers, CLOCK was reported to have a regulatory role in breast cancer tumorigenesis [ 21 , 22 ], while no specific studies have reported the role of GTF3C4 in breast cancer. For the two erasers, overexpression of HDAC2 had a strong effect on breast cancer prognosis [ 23 , 24 , 25 ] while the effect of SIRT7 seems to be controversial [ 26 , 27 , 28 ]. Moreover, the writer genes were found to be more highly expressed in HAM2 than in HAM1 while the erasers showed the opposite trend.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of protein expression levels of SCGB2A1 in UCEC was performed by UALCAN based on the CPTAC database. UALCAN performed the comparison of differential expression between each two groups by using t-tests (22), and similar results from the UALCAN using the same statistical methods have been published previously (23)(24)(25). Differential protein expression of SCGB2A1 between UCEC and normal tissues, and the association between clinical characteristics and protein expression levels of SCGB2A1, were analyzed.…”
Section: Clinical Proteomic Tumor Analysis Consortium (Cptac)mentioning
confidence: 99%